Development of Edible Carbohydrate–Protein Sports Gels to Optimize the Muscle Glycogen Re-Synthesis - Vishal Verma; Vishal Gill; Avinash Kumar; Shailendra Pratap Singh (Gels)
This study was aimed at providing athletes a solution to replenish the muscle glycogen re-synthesis at an optimal rate with hemp seeds as a natural protein source and Bengal gram dal and its use for the preparation of gel. The gel contains the richest source of energy, and it is an effective way to provide energy and nutrients to athletes. The gel was prepared in three variations with different hemp seed concentrations. We then analyzed the gel for pH and macronutrient composition. The sensory characteristics were analyzed for seven parameters, including appearance, taste, color, texture, aroma, consistency, and acceptability, using a hedonic scale on 25 panelists. A sensory analysis showed that sample A received an overall acceptability score of 7.16 ± 0.99 from the sensory panel. The shelf life was observed at the recommended temperature of 4 degrees Celsius, which was 12 days. The best formulation was sample B with 38 g of hemp seeds, which showed better taste, color, aroma, and acceptability and a lower average pH value (6.68 ± 1.44, 6.56 ± 1.29, 7.6 ± 1.16, 7 ± 1.26, and 5.822 ± 0.0183, respectively). Sample B contained 30.8 g of protein, 16.09 g of carbohydrates, 8.4 g of fat, and 263.16 kcal of energy per 100 g. The resulting ratio of carbohydrates to protein is optimal for use as a high-protein post-workout meal. Hence, it can be considered a post-workout supplement.